In vitro propagation of Silene bolanthoides Quézel, Contandr. & Pamukç. and assessment of genetic stability by flow cytometry - Çördük, Nurşen; Yücel, Gülru; Akıncı, Nihan; Tuna, Metin; Esen, Onur (Archives of Biological Sciences, 2018)
Silene bolanthoides Quézel, Contandr. & Pamukç. is an endemic species from Kazdagi (Mt. Ida), Canakkale-Balikesir, Turkey. In order to develop an efficient shoot regeneration protocol, the leaf, nodal and internodal explants of S. bolanthoides were cultured on Murashige and Skoog (MS) medium containing benzyladenine (BA) alone or in combination with α-naphthaleneacetic acid (NAA). The highest number of regenerated shoots (5.75±0.1) was obtained from nodal explants that were cultured on MS medium with 8.8 µM BA+0.54 µM NAA. Regenerated shoots were rooted on MS medium without plant growth regulators (PGRs). Rooted plants (2-3 cm) were separately transferred to pots containing a mixture of peat and perlite (3:1 v/v) and acclimatized successfully in a growth chamber. Genetic stability of the propagated plants was assessed by flow cytometry and cytological analysis. Flow cytometry analysis demonstrated that regenerated plants had 2.61±0.01 pg nuclear DNA (2C) and seed-derived plants had on average 2.58±0.02 pg/2C. Cytological analysis showed that the regenerated plants had the same chromosome number as seed-derived plants of S. bolanthoides (2n=24). It was determined that regenerated plants were uniform in chromosome number and had a similar DNA content to the seed-derived ones, indicating that the described efficient shoot regeneration protocol can be applied for ex situ conservation of this species. https://doi.org/10.2298/ABS170410033C Received: April 10, 2017; Revised: August 9, 2017; Accepted: August 16, 2017; Published online: September 12, 2017 How to cite this article: Çördük N, Yücel G, Akıncı N, Tuna M, Esen O. In vitro propagation of Silene bolanthoides Quézel, Contandr. & Pamukç. and assessment of genetic stability by flow cytometry. Arch Biol Sci. 2018;70(1):141-8.